THE NEW INTERNAL REVENUE ACT AND THE PROSPERITY OF THE ECONOMY. - Carlson, A. B. (The Accounting Review, 1956)
This article focuses on new internal revenue act and the prosperity of the economy of United States. The devices to stimulate enterprise, employment and prosperity, five features are set forth. They are: the extension to two years of the carry-back for net business losses, the modifications in the taxation of dividend income received by individuals, the provisions for accelerated depreciation, provisions for deduction of research and development expenditures and the relaxation of provisions relating to the taxation of undistributed earnings of corporations. The author suggests that perhaps this new code should be looked upon as the first step, or the first few steps, toward a tax system that gives more attention to economic incentives. These features offer some promise of helping. It would be a mistake to regard them as anything more than helpers. They are only a part of an intricate tax system. The system itself is not an all-purpose economic tool, it is only one of several regulators in the economy.